First occurrence of cylindrospermopsin in Portugal: a contribution to its continuous global dispersal - Moreira C. (2017)
Cylindrospermopsin (CYN) was found to occur in Portugal for the first time. In this study CYN values varied from a minimum of 1.4 μg L−1 to a maximum of 12 μg L−1 detected through HPLC technique and confirmed by LC-MS method. Amplification of the cyrC gene was done and was confirmed to be from the genera Aphanizomenon. This study is therefore an important contribution to the knowledge on the dispersal and biogeography of CYN. © 2017